DIFFERENCE IN WHITE BLOOD CELL COUNT IN STUDENTS CONSUMING HIGH-PROTEIN MILK AND THOSE NOT CONSUMING IT AT SMK MA'ARIF NU 2 AJIBARANG - Adzani Azhar, Fadlilah; Farabi, Meka Faizal; Nugroho, Yusuf Eko (Jurnal Mitra Kesehatan, 2026)
Introduction : Leukocytes are an important part of the immune system that plays a role in fighting infection. Adequate protein intake, including from high-protein milk such as goat's milk, is believed to support the formation and function of leukocytes in the body. The protein, vitamin, and mineral content in goat's milk is known to play a role in supporting the immune system. This study aims to determine the difference in white blood cell counts between female students who consume high-protein goat milk and those who do not. Method: This study was conducted over a period of six months, from December to May 2025, at the TLM laboratory of SMK Ma'arif NU 2 Ajibarang. The research was conducted experimentally using a post-test only control group design on 28 female students in class XI TLM SMK Ma'arif NU 2 Ajibarang who were randomly selected using simple random sampling from the entire student population of the school, then divided into two groups, namely the treatment group (consuming high-protein goat milk) and the control group (not consuming). Data were obtained from examining the number of leukocytes using a manual method with an Improved Neubauer counting chamber. Result: The results showed that the average leukocyte count in the treatment group was 7946.43 cells/micoL, whereas in the control group it was 5885.71 cells/microL. The Independent Sample T-Test yielded a p- value rather than 0.001, which shows that there is a significant difference between the two groups. Conclusion: High consumption of protein-rich milk has a significant effect on increasing the number of leukocytes, making it a viable alternative for supporting the immune system of adolescent girls.